Singularidades e diversidades do artesanato norte-rio-grandense - Alessandro Dozena (Confins)
The understanding of the construction of local development strategies backed by creativity reveals that social practices are the condition for a more dignified life, and a counterpoint to the hegemonic restructuring movement. This is the case of craft activities, adding value to the business from actions with a strong link between traditions, local customs, knowledge and actions; which end up being incorporated into the handcrafted products. In the state of Rio Grande do Norte, productive restructuring was accompanied by transformations in the ways of life in small and medium-sized municipalities, and new spatial arrangements that emerged from creative economies and community based organizations. Such arrangements bring together political, economic and social agents directed to economic activities with cooperative links, although usually precarious. For the elaboration of this article, we carried out the bibliographical survey, the reading and contextualization with the bibliography related to the theme, the identification of the artisan activities in the state of Rio Grande do Norte, besides interviews with thirteen women crafts.